2010
DOI: 10.1002/bmb.20385
|View full text |Cite
|
Sign up to set email alerts
|

New ideas for an old enzyme: A short, question‐based laboratory project for the purification and identification of an unknown LDH isozyme

Abstract: Enzyme purification projects are an excellent way to introduce many aspects of protein biochemistry, but can be difficult to carry out under the constraints of a typical undergraduate laboratory course. We have designed a short laboratory project for the purification and identification of an ''unknown'' lactate dehydrogenase (LDH) isozyme that can fit into a multiproject course without consuming too many laboratory days. The streamlined purification utilizes ammonium sulfate precipitation, affinity chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…As it was recently pointed out [6], hands-on experience with performing experiments and analyzing data helps students to develop problem-solving skills that will benefit them throughout their life. And according to a popular editorial in Science [17] such problem-solving skills are not being adequately taught to undergraduate students, the result of too much focus on presenting scientific explanations without covering the scientific processes and reasoning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was recently pointed out [6], hands-on experience with performing experiments and analyzing data helps students to develop problem-solving skills that will benefit them throughout their life. And according to a popular editorial in Science [17] such problem-solving skills are not being adequately taught to undergraduate students, the result of too much focus on presenting scientific explanations without covering the scientific processes and reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…LDH screening assay (spot test). This quick evaluation of the presence of LDH activity using a 96-well plate was adapted from [6]. Creation of NADH in the presence of LDH drives the successive reduction of phenazine methosulphate (PMS) and then p-iodo nitrotetrazolium (INT).…”
Section: Protein and Activity Content Of The Fractionsmentioning
confidence: 99%
“…Some other studies have also found the relationship of creative thinking skills to experimental activities in the lab. Experimental activities can make students do a practicum with hands on as well as minds on activity (Bellin, Bruno, and Farrow, 2010;Coleman, 2010;Witherow and Carson, 2011;Trapani and Clarke, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We chose the enzyme lactate dehydrogenase (LDH) as the target molecule for isolation and electrophoretic characterization. While previous papers and laboratory manuals , have described the isolation of this protein from mammalian heart or skeletal muscle, we chose to do the isolation from mammalian blood, a nontraditional source that offers a number of advantages. (1) Red blood cells (RBC) are easily isolated in pure form from whole blood by repeated centrifugation in isotonic saline; (2) the cytosolic fraction, or membrane-free lysate, is generated by simple hypotonic lysis followed by centrifugation; (3) the resulting lysate yields LDH activity that is stable for several weeks, allowing a measure of flexibility with regard to the timing of its preparation for the class; (4) the lack of any significant protease activity in the lysate alleviates the need to add expensive and toxic protease inhibitors; (5) the fold purification and percentage recovery of activity are far superior to those typically reported for the isolation of LDH using mammalian muscle tissues. …”
Section: Introductionmentioning
confidence: 99%